Specific Pathogen Recognition by Multiple Innate Immune Sensors in an Invertebrate - Tetreau, Guillaume; Pinaud, Silvain; Portet, Anaïs; Galinier, Richard; Gourbal, Benjamin; Duval, David (Frontiers in Immunology, 2017)
Detection of pathogens by all living organisms is the primary step needed to implement a coherent and efficient immune response. This implies a mediation by different soluble and/or membrane-anchored proteins related to innate immune receptors called PRRs (pattern recognition receptors) to trigger immune signaling pathways. In most invertebrates, their roles have been inferred by analogy to those already characterized in vertebrate homologues. Despite the induction of their gene expression upon challenge and the presence of structural domains associated with the detection of pathogen-associated molecular patterns (PAMPs) in their sequence, their exact role in the induction of immune response and their binding capacity still remain to be demonstrated. To this purpose, we developed a fast interactome approach, usable on any host-pathogen couple, to identify soluble proteins capable of directly or indirectly detecting the presence of pathogens. To investigate the molecular basis of immune recognition specificity, different pathogens (gram positive bacterium: Micrococcus luteus, gram negative: Escherichia coli, yeast: Saccharomyces cerevisiae, and metazoan parasites: Echinostoma caproni or Schistosoma mansoni) were exposed to hemocyte-free hemolymph from the gastropod Biomphalaria glabrata. Twenty-three different proteins bound to pathogens were identified and grouped into three different categories based on their primary function. Each pathogen was recognized by a specific but overlapping set of circulating proteins in mollusk’s hemolymph. While known PRRs such as C-type lectins were identified, other proteins not known to be primarily involved in pathogen recognition were found, including actin, tubulin, collagen and hemoglobin. Confocal microscopy and specific fluorescent labeing revealed that extracellular actin present in snail hemolymph was able to bind to yeasts and induce their clotting, a preliminary step for their elimination by the snail immune system. Aerolysin-like proteins (named biomphalysins) were the only ones involved in the recognition of all the five pathogens tested, suggesting a sentinel role of these horizontally-acquired toxins. These findings highlight the diversity and complexity of a highly specific innate immune sensing system. It paves the way for the use of such approach on a wide range of host-pathogen systems to provide new insights into the specificity and diversity of immune recognition by innate immune systems.